Bacterial culture through selective and non-selective conditions: the evolution of culture media in clinical microbiology. (March 2020) - Bonnet, M.; Lagier, J.C.; Raoult, D.; Khelaifia, S.
Abstract: Microbiology has been largely developed thanks to the discovery and optimization of culture media. The first liquid artificial culture medium was created by Louis Pasteur in 1860. Previously, bacterial growth on daily materials such as some foods had been observed. These observations highlighted the importance of the bacteria's natural environment and their nutritional needs in the development of culture media for their isolation. A culture medium is essentially composed of basic elements (water, nutrients), to which must be added different growth factors that will be specific to each bacterium and necessary for their growth. The evolution of bacterial culture through the media used for their culture began with the development of the first solid culture medium by Koch, allowing not only the production of bacterial colonies, but also the possibility of purifying a bacterial clone. The main gelling agent used in solid culture media is agar. However, some limits have been observed in the use of agar because of some extremely oxygen-sensitive bacteria that do not grow on agar media, and other alternatives were proposed and tested. Then, the discovery of antimicrobial agents and their specific targets prompted the emergence of selective media. These inhibiting agents make it possible to eliminate undesirable bacteria from the microbiota and select the bacteria desired. Thanks to a better knowledge of the bacterial environment, it will be possible to develop new culture media and new culture conditions, better adapted to certain fastidious bacteria that are difficult to isolate.